The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2903/j.efsa.2018.5176
|View full text |Cite
|
Sign up to set email alerts
|

Lumpy skin disease II. Data collection and analysis

Abstract: The spatial and temporal patterns of lumpy skin disease (LSD) epidemics were analysed based on the data collected from affected and at-risk countries in southeastern Europe in 2016 and 2017. The reported outbreaks decreased from 7,483 in 2016 to 385 in 2017. Those were reported mainly in Albania in areas where vaccination was not completed. Only two and four outbreaks were reported in Greece and in the former Yugoslav Republic of Macedonia in 2017, respectively, where the herd immunity achieved by vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Vaccination is the most effective way to prevent the spread of the infection in endemic and newly affected regions. Indeed, studies have shown that several countries in southeastern Europe and Israel have successfully prevented LSDV incursions by vaccinating the susceptible population [ 31 ]. Yet, in the event of an outbreak, selection of the best vaccine presents a significant challenge for veterinary authorities and farmers.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination is the most effective way to prevent the spread of the infection in endemic and newly affected regions. Indeed, studies have shown that several countries in southeastern Europe and Israel have successfully prevented LSDV incursions by vaccinating the susceptible population [ 31 ]. Yet, in the event of an outbreak, selection of the best vaccine presents a significant challenge for veterinary authorities and farmers.…”
Section: Discussionmentioning
confidence: 99%
“…among study groups). To estimate the effectiveness of vaccination, the probability of exposure of vaccinated and non‐vaccinated flocks to the field virus should be similar on average (EFSA, 2018 ; Klement et al., 2020 ). Given that vaccination is expected to be applied in those regions most at risk, it would be difficult to have all those conditions in place.…”
Section: Assessmentmentioning
confidence: 99%
“…As it is a fulminating infectious disease, the World Organization for Animal Health (OIE) stipulates LSD is the communicable disease that must be reported. LSDV can spread in many ways, such as indirect contact transmission between animals through vectors, lactation spread, blooding feeding insects, semen spread and iatrogenic transmission ( Weiss, 1968 ; Carn and Kitching, 1995 ; Mullen and Durden, 2002 ; Annandale et al, 2010 ; European Food Safety Authority, 2018 ). Some researchers have conducted experiments to confirm that the disease is difficult to spread through direct contact ( Carn and Kitching, 1995 ; Magori-Cohen et al, 2012 ; Mulatu and Feyisa, 2018 ).…”
Section: Introductionmentioning
confidence: 99%